Prevalence of Intestinal Parasitic Infections and Associated Factors Among Food Handlers in Wolaita Sodo University Students Caterings, Wolaita Sodo, Southern Ethiopia: A Cross-Sectional Study - Kumma, Wondimagegn P.; Meskele, Wubshet; Admasie, Amha (Frontiers in Public Health, 2019)
Background: Intestinal Parasitic Infections (IPIs) are among the most prevalent diseases in the world, particularly in developing countries with low socio-economic and poor living conditions. From the estimated one third global population infected by intestinal parasitic infections; the majority lives in tropical and sub-tropical parts of the world. These diseases are highly prevalent in Ethiopia. However, its magnitude in the context of Wolaita Sodo University, where a large number of students reside in a campus is not studied. Therefore, the objective of this study was to assess the prevalence and factors associated with intestinal parasitic infections among food handlers in students' caterings of Wolaita Sodo University, Southern Ethiopia. Methods: Institutional based cross sectional study was conducted among food handlers working in Wolaita Sodo University students' caterings' from January 10 to February 10, 2016. The study was undertaken among 233 food handlers by using simple random sampling technique. Data were collected using structured and pretested questionnaire; observation of food handlers while working and microbiological laboratory investigations. Bivariate and multivariate analyses were used to assess the association between covariate and the outcome variables. Adjusted Odds Ratio (AOR) with 95% confidence interval (CI) was considered to ascertain the significance of the association. Results: The mean age of the study participants was 27.2 (±6.4 SD). The overall prevalence of intestinal parasitic infections was 23.6%, with 95% CI of 18.2% to 29.1% of which 12.4% was due to amoeba cyst. Untrimmed fingernail with AOR (95% CI) 2.06 (1.06, 4.00) and regular hand washing habit without soap before food handling with AOR (95% CI) 2.68 (1.25, 5.73) were found to be significantly associated with intestinal parasitic infections. Conclusions: The prevalence of intestinal parasitic infections was high among Wolaita Sodo University food handlers. Untrimmed fingernail and hand washing habit without soap before food handling were found to increase odds of intestinal parasitic infections. The university may need to consider interventions recommended accordingly.